RELATIONSHIP BETWEEN DIGITAL GREEN MARKETING, EASE OF APPLICATION, CUSTOMER SATISFACTION, AND CUSTOMER LOYALTY - Catur Palupi; Eko Budi Satoto; Retno Endah Supeni (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
The era of globalization is the basis for the increasing use of mobile banking services and the demand for the application of sustainability principles in banking marketing practices, especially in the BRImo application. Green digital marketing and ease of use of applications are seen as important factors that can affect customer satisfaction and loyalty in the current era of digital banking transformation. This study uses a quantitative approach with a survey technique to customers who use the BRImo application as respondents, where data is collected through a structured questionnaire and analyzed to test the influence of digital green marketing and ease of application on customer satisfaction and loyalty, including the role of satisfaction as a mediating variable. The results of the study show that green digital marketing and ease of application have a positive and significant effect on customer satisfaction of BRImo users, which further strengthens customer loyalty, as well as that these two variables also have a significant direct influence on loyalty. This study aims to analyze the influence of Green digital marketing and ease of application on customer loyalty of BRImo users, both directly and indirectly through customer satisfaction as a mediation variable